'FLIP' A METHOD FOR PLANNING COMMUNITY SAFETY PROMOTION PROGRAMMES: FINDING THE RIGHT TREATMENT BEGINS BY MAKING THE RIGHT DIAGNOSIS. (7th October 2012) - Hanson, D; Lloyd, J; Gunning, C; Rose, J
Abstract : Background: Designing effective safety promotion programmes is about finding creative solutions to the tension between visionary dreams and practical solutions. Nothing will be achieved unless you have the vision to imagine a better reality for yourself, your family, your friends and your community, but nothing can be achieved unless you have the pragmatism to seek out effective solutions. Big problems must be broken down into components that can be solved. Big plans must be broken down into incremental steps that can be achieved. Aims/Objectives/Purpose: This workshop will demonstrate 'FLIP', a comprehensive system for helping communities design effective evidence based safety promotion programmes. Method: 'FLIP' guides participants through six simple steps that culminate in the formulation of a comprehensive project plan. 1. Identify the problem, then 'FLIP' to your goal. 2. Analyse the problem. 3. Having identified the key causes of the problem, 'FLIP' to your objectives. 4. Find solutions to achieve your objectives. 5. Implement the programme. 6. Evaluate the programme. Results/Outcomes: Unfortunately, the same mistake is made over and over again. People race to the solutions before taking the time to understand the problem. This is a guaranteed way to end up solving the wrong problem! It's not hard, provided you remember to 'FLIP'. Start by making sure you understand the problem, then 'FLIP' to the solutions. Significance/Contribution to the Field: By eliminating needless jargon, 'FLIP' seeks to facilitate an open transdisciplinary dialogue in which everyone, researchers, practitioners and the target community, can constructively contribute to the planning process.